The Qualification of Action in Administrative Justice and its Perils – the Czech Experience - Svoboda, Tomáš; Skládalová, Denisa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
This paper concerns the system of the ‘main’ types of administrative action in the Czech administrative justice, more precisely the qualification of the ‘correct’ type of an action. The boundaries between action types are not always clear, which has consequences for the protection of applicants’ rights in the administrative justice proceedings. The first part of the paper deals with the theoretical level of the problem outlined. The second part deals with some recent changes in Czech case law and proposes possible solutions.